Role of Phosphorus and Inoculation with Bradyrhizobium in Enhancing Soybean Production - Akello Mirriam; Jayne Mugwe; Jamal Nasar; Oscar Kisaka; Shivani Ranjan; Harun Gitari (Advances in Agriculture)
Soybean (Glycine max L. Merril) is among the key oil seed crops worldwide, providing several benefits from human consumption to the enhancement of soil productivity. In Uganda, legumes are cultivated on roughly 1.5 million ha, with soybean being produced on a lower production area of 150,000 ha compared to beans (925,000 ha) and groundnuts (253,000 ha). In terms of achievable yield, soybean emerges the highest at 1.2 t·ha−1 as compared to beans (0.5 t·ha−1) and groundnuts (0.7 t·ha−1). Despite the smallest production coverage area, the crop’s feasible grain yield is projected at 4.6 t·ha−1 under optimal environmental conditions. The major bottleneck to the crop’s production is the decreasing soil fertility, mainly caused by low nitrogen (N) but also phosphorus (P) levels in the soil. There is a high potential for supplying N from the atmosphere through biological N fixation (BNF), a natural process mediated by the symbiotic bacteria Bradyrhizobium japonicum, which requires optimum P levels for effective N fixation and increased yield. The current work reviews the present status of soybean production in Uganda, highlights its ecological requirements, importance, and constraints, and proposes the use of inoculation and P application to boost its production.